Peran Kolaborasi Galeri, Perpustakaan, Arsip dan Museum Dalam Mendiseminasikan Sumber Informasi Pengetahuan kepada Masyarakat - Tupan Tupan; Mohamad Djaenudin (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2022)
An analysis of the role of galleries, libraries, archives and museums as a source of information for public knowledge was conducted. This study aims to find out how the collaborative role of galleries, libraries and archives in disseminating knowledge information sources to the public. The study was conducted using a narrative review which was complemented by observations via the web. The results of the analysis show that institutions that have collaborated include merging and collaborating with regional libraries and archives located in provinces and districts as well as cities throughout Indonesia. The libraries and galleries that have joined are the Fiction Literacy Library and Gallery in Surabaya. For libraries and museums that have joined or collaborated are the Zoological Museum, Tobacco Library and Museum, Soil and Agriculture Museum, and the Geological Museum. As for the combination or collaboration of museums and galleries, they are the Natural History Museum and the Youth Pledge Museum. Referring to the merger between libraries and archives, between libraries and museums, as well as between museums and galleries, it is hoped that the concept of merging or convergence of the roles of galleries, libraries, archives and museums in disseminating regulatory science and technology to the public.